2014
DOI: 10.1111/1756-185x.12339
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sleep problems in children with familial Mediterranean fever

Abstract: This study showed for the first time that children with FMF had more sleep disturbances than their healthy peers. Higher numbers of attacks and exertional leg pain were associated with poor sleep quality. In conclusion, this study underlines the need to assess and manage sleep problems in children with FMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 39 publications
2
25
1
Order By: Relevance
“…Patients with a higher number of attacks were noted to experience difficulty in falling asleep, more night wakings and sleep-disordered breathing. 9 In our study, mean total PSQI score of FMF patients was 5.74 AE 3.08 and 41.13% of patients had poor sleep quality. These results are comparable to reported incidence of sleep disorder in other rheumatologic conditions.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…Patients with a higher number of attacks were noted to experience difficulty in falling asleep, more night wakings and sleep-disordered breathing. 9 In our study, mean total PSQI score of FMF patients was 5.74 AE 3.08 and 41.13% of patients had poor sleep quality. These results are comparable to reported incidence of sleep disorder in other rheumatologic conditions.…”
Section: Discussionmentioning
confidence: 45%
“…showed that sleep quality of pediatric FMF patients was negatively affected by the number of attacks. Patients with a higher number of attacks were noted to experience difficulty in falling asleep, more night wakings and sleep‐disordered breathing …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations